ENGARUH KUALITAS AUDIT TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Mira Mira; A. Wirta Purnamasari (Jurnal Riset Perpajakan: Amnesty, 2020)
This study aims to determine how the effect of audit quality on Tax Avoidance in banking sector companies listed on the Indonesia Stock Exchange (BEI) by using control variables (Company Size and Leverage). This type of research used in this research is descriptive quantitative. The data analysis technique used in this research is descriptive statistical analysis, classical assumption test and multiple regression analysis. The sampling technique in this study used purposive sampling and obtained 27 banking companies with an observation period of 3 (three) years in order to obtain 81 sample units in this study. Based on the results of data analysis, it can be concluded that Audit Quality has a significant negative effect on Tax Avoidance. This means that the higher the audit quality, the lower the tax avoidance.